Role of donor HLA class I mismatch, KIR‐ligand mismatch and HLA:KIR pairings in hematological malignancy relapse after unrelated hematopoietic stem cell transplantation. (21st December 2018) - Graczyk‐Pol, Elzbieta; Rogatko‐Koros, Marta; Nestorowicz, Klaudia; Gwozdowicz, Slawomir; Mika‐Witkowska, Renata; Pawliczak, Daria; Zubala, Marta; Szlendak, Urszula; Witkowska, Agnieszka; Tomaszewska, Agnieszka; Nasilowska‐Adamska, Barbara; Szczepinski, Andrzej; et al.
Abstract : HLA are functional in cancer immunosurveillance in adaptive and innate immunity pathways. In unrelated hematopoietic stem cell transplantation (HSCT) in 688 patients with hematological malignancies we compared antitumor efficacy of transplant in three models including the level of: (a) donor‐recipient HLA class I mismatch, (b) KIR‐ligand mismatch, (c) post‐transplant cognate HLA:KIR pairing. The effects were directly compared in multivariate models with backward elimination including all three effects in initial model. In final multivariate model HLA mismatch and KIR‐ligand mismatch levels were eliminated and HLA:KIR‐dependent NK cell licensing effect remained independent prognostic factor for DFS, relapse/progression incidence, and overall survival (OS). These results suggested that NK cell licensing via cognate HLA:KIR pairs is primarily functional in cancer immunosurveillance in HSCT.